Exploring the potential of Amberlite IRA-402 in the adsorption of emerging pharmaceutical contaminants in aqueous solution - Boulett-Neira, A; Boulett-Neira, A (ELSEVIER, 2026)
This study assessed the adsorption performance of Amberlite IRA-402 cationic resin for removing amoxicillin (AMX) and tetracycline (TC) from water. Adsorbent dosage and pH were simultaneously optimized through experimental design, identifying 10 mg resin at pH = 10.0 as optimal. The influence of contact time, initial concentration of antibiotic, and temperature was examined, fitting kinetic, isotherm, and thermodynamic models. AMX showed faster adsorption and a higher maximum capacity (512 mg g-1) than TC (488 mg g-1). AMX followed the pseudo-first-order model, while TC better fitted the Elovich model, indicating heterogeneous surface adsorption. Both antibiotics matched the Redlich-Peterson model, suggesting mixed adsorption mechanisms. Adsorption was endothermic and spontaneous above 288 K. Salt interference tests revealed greater TC sensitivity to multivalent anions. The resin showed a good performance for at least four adsorption-desorption cycles. Application in simulated hospital effluent confirmed its efficacy. Post-adsorption characterization by FTIR identified the main functional groups of the resin and antibiotics, including specific AMX and TC signals. Scanning electron microscopy showed increased surface roughness after adsorption, evidencing morphological changes. These findings highlight the potential of Amberlite IRA-402 as a versatile adsorbent, encouraging further exploration with other contaminants for broader water treatment applications.